Implementation of English Learning Based on Multiple Intelligences on English Speaking Ability - Ida Maulida (Jurnal Scientia, 2021)
This study was conducted to describe the use of the Multiple Intelligences method in learning English in schools. This study uses a descriptive method with a qualitative approach and the results of this study explain that, the development of Multiple Intelligences which is supported by curriculum, learning materials, human resources and learning processes that have been adjusted previously, is designed to develop intelligence and skills in students, especially in language skills ( speaking, writing, listening, reading) through the Multiple Intelligences method, with very varied, fun and creative activities. The learning begins by fully explaining the method that will be applied, then the teacher will make a lesson plan, where the preparation of this lesson plan is done by integrating English subjects with the method that will be used. The lesson plan consists of three parts, namely: syllabus (Title, Indicator, Time allocation) then the second component of activity (preliminary activity) and the last core activity (activity strategy and procedures). The effect of the implementation of the Multiple Intelligences-based English learning model on vocabulary mastery and English speaking skills and its impact on the results of the learning implementation and student learning experience can be seen from the students' motivation in participating in English learning, overall this method can be followed well by all students start from core activities which include exploration, elaboration, and confirmation of Multiple Intelligences-based learning activities, and closing activities which include reflection and evaluation. The procedure in implementing English learning in the classroom is emphasized on reading, writing, and listening skills with core activities such as discussion and dialogue.